Situation of obstetric fistula in a marginalized teagarden community of Bangladesh: A Qualitative Study. - Abdullah, Abu Sayeed Md. (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To explore the situation of obstetric fistula among the teagarden women in Bangladesh. Methods: A qualitative study was conducted. During the screening, a total number of five obstetric fistula cases identified from the 10 teagardens covering around 50 thousand populations. The study performed in depth face to face interview with the all women with a guideline. Results: The mean age was 41 years. All were married before 15 years of age and delivered the following year. Obstructed labour was the reason for fistula in all cases. Mean duration of suffering was 19 years. One woman is found divorced, two woman’s husband leaves her and two is continuing her conjugal life. In all cases, husband separated and women were living alone. Only one woman receiving treatment from a tertiary facility left treatment due to economic crisis. The other causes of not receiving treatment include lack of knowledge and its treatment, misperception of self recovery, negligence, lack of time due to job at teagarden, ignorance, transportation and economic crisis. All women faced serious negligence and were culturally restricted to attend the family or religious programme. All women wanted to be cured. Conclusions: Focused intervention is required to eliminate obstetric fistula, very small number of cases flag many stories. It is likely teagarden catchment areas in Bangladesh is vulnerable with obstetric fistula cases which are still unexplored. It’s important to know actual epidemiology of obstetric fistula in the teagarden community, on the other hands it also demands for establishment of timely referral pathway, proper management system including rehabilitation and reintegration in order to reduce or eliminate obstetric fistula in Bangladesh by 2030.